Developing Project-Based Learning Modules on Ponoragan Culture in the Merdeka Curriculum for Early Childhood Education - Betty Yulia Wulansari; Ardhana Januar Mahardhani; Nurtina Irsad Rusdiani; Siti Khoirul Bariyah; Ryan Juppenny (AL-ISHLAH: Jurnal Pendidikan, 2025)
Preserving local culture through early childhood education is a strategic step in sustaining national identity. The Merdeka Curriculum emphasizes project-based learning (PjBL) through the Strengthening Pancasila Student Profile (P5) framework, offering opportunities to integrate cultural heritage into early learning. However, cultural representation in ECE, particularly of Ponoragan traditions, remains limited. This study employed a Research and Development (RD) design to create PjBL modules rooted in Ponoragan culture for Early Childhood Education (ECE). The development process included a preliminary cultural and curriculum review, module design aligned with P5 principles, and expert validation by ECE practitioners, cultural experts, and curriculum specialists. Data were collected through interviews, observations, and validation questionnaires, then analyzed descriptively. Four thematic modules were developed: Wonderful of Reyog Ponorogo, Gajah Wengker Cultural Heritage, Keling Guno Joyo Dance, and Gong Gumbeng Wringinanom. Each module included structured activities such as outings, STEAM-based projects, visual literacy, and performance exhibitions. Expert validation confirmed their cultural relevance, feasibility, and alignment with curriculum goals, including development of children's moral values, identity, creativity, and collaboration. The modules demonstrate potential in fostering cultural literacy and Pancasila values from an early age. Despite successful validation, broader implementation and empirical impact assessments remain areas for further study. This research contributes a culturally responsive curriculum model for ECE, supporting both educational development and cultural preservation under the Merdeka Curriculum framework.